Attention-deficit hyperactivity disorder medication shortage in the United States: a qualitative assessment of Reddit posts - Shrestha, Shikhar; Varghese, Shama; Mehta, Simran; Dev, Saloni (Frontiers in Pharmacology, 2025)
IntroductionApproximately 6% of the US population had been diagnosed with attention-deficit hyperactivity disorder (ADHD) in 2023, and approximately 33% of the patients received stimulants to manage it. Recent ADHD medication shortages in the United States have caused substantial disruptions in access to these medications. The objective of our study was to investigate how individuals respond psychologically and behaviorally to ADHD medication shortage in the United States using public discussions on Reddit.MethodsWe extracted Reddit threads from “r/ADHD” that consisted of the keyword “shortage.” After identifying relevant threads, we qualitatively analyzed 16 threads relevant to our study to reach thematic saturation. We used a hybrid inductive–deductive thematic analysis grounded in stress and coping theory to perform a qualitative analysis of the posts between August 2021 and February 2024.ResultsOur findings show that redditors consuming ADHD medication experienced significant cognitive, emotional, and functional impacts due to medication shortage (primary appraisal). Redditors reported challenges with accessing medication due to complex medical systems, unsupportive healthcare providers, financial strain, and limited understanding of the causes of the shortage (secondary appraisal). Redditors also reported a range of pharmacological (change in dosage/medication, skipping dosage, saving medication, caffeine, and nicotine) and non-pharmacological (meditation and exercise) changes to behavior to manage the shortage (coping strategies). In addition, the Reddit community fostered support, positivity, and resource-sharing to navigate the shortage.ConclusionOur study highlights the urgent need for healthcare policies that support individuals with ADHD amid shortages, emphasizing the role of transparent communication from pharmacies, healthcare providers, and regulatory bodies.